MELACAK TERMINOLOGI MANUSIA DALAM ALQURAN - Rizal, Syamsul (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
This article aims to discuss human concepts in the Quran. Allah SWT. call Human Beings in the Quran there are several terminologies such as basyar, insan, unas, insiy, imru, rajul or which contain the meaning of women such as imraah, nisa or niswah or in personality traits, such as al-atqa, al-abrar, or ulul albab, also as part of social groups such as al-asyqa, dzul-qurba, al-dhuafa who all contain instructions as human beings in their essence and humans in concrete forms. Humans are the most perfect creatures that Allah SWT has ever created. The purpose of creating humans is only to worship Allah SWT, and to become a caliph on earth.